2020
DOI: 10.3389/fgene.2020.00366
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Investigation of Island Jersey Cattle, the Foundation of the Jersey Breed: Comparing Population Structure and Selection to Guernsey, Holstein, and United States Jersey Cattle

Abstract: For two centuries, Jersey cattle were exported globally, adapting to varying climates and production systems, yet the founding population remained genetically isolated on the Island of Jersey. The Island of Jersey formally allowed the importation of pure Jersey cattle in 2008. This study characterized the genetic variation of 49 popular bulls from the Island of Jersey born from 1964 to 2004 and compared them to 47 non-Island Jersey bulls and cows, primarily from the United States In addition, 21 Guernsey cattl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
4
14
0
Order By: Relevance
“…We observed slight excess of heterozygotes in both the Russian breeds ( U F IS = -0.022 and -0.013 for Kholmogor and Yaroslavl breeds, respectively), which agrees with the findings obtained using DNA chips of lower density [9,10]. The detected inbreeding coefficient in Holsteins ( U F IS = -0.010) was similar or lower than one which was discovered in recent reports (F IS = −0.004 [60], F IS = 0.0526 [15]), which might reflect the differences in sample origins and population sizes.…”
Section: Plos Onesupporting
confidence: 90%
“…We observed slight excess of heterozygotes in both the Russian breeds ( U F IS = -0.022 and -0.013 for Kholmogor and Yaroslavl breeds, respectively), which agrees with the findings obtained using DNA chips of lower density [9,10]. The detected inbreeding coefficient in Holsteins ( U F IS = -0.010) was similar or lower than one which was discovered in recent reports (F IS = −0.004 [60], F IS = 0.0526 [15]), which might reflect the differences in sample origins and population sizes.…”
Section: Plos Onesupporting
confidence: 90%
“…Figure 1 indicated that Slovak Spotted and Ayrshire populations were partially linked together probably due to use of Ayrshire in the grading-up of Slovak Spotted. Huson et al (2020) reported for Jersey cattle bred in different areas homogeneity despite a various geographic origin, compared with Holstein and Guernsey. In contrary, Ahmad et al (2020) found among breeds Holstein, Jersey and Brown Swiss high degree of differentiation depending on the geographical origin.…”
Section: Resultsmentioning
confidence: 93%
“…At K = 4, a light green taurine ancestry was highlighted in the JER breed. This could be explained by the fact that this breed was only "discovered" around 200 years ago in the Jersey island, and this fact could have contributed to the maintenance of a conserved and distinct genetic composition of this breed, especially when compared with HOL, as also observed by Huson et al (2020).…”
Section: Discussionmentioning
confidence: 99%